Prevalence and Associated Factors of Alcoholism among Tuberculosis Patients in Udupi Taluk, Karnataka, India: A Cross Sectional Study - Thapa, P; Kamath, R; Shetty, B K; Monteiro, A; Sekaran, V C (Journal of Nepal Health Research Council, 2015)
Background: Tuberculosis (TB) is a major public health problem in India. Several studies carried out in India have shown alcoholism as a risk factor for tuberculosis mortality, factor for default in TB and reason for non-compliance under the Revised National Tuberculosis Control Program (RNTCP). The aim of this study was to assess the prevalence, pattern and associated factors of alcohol use among tuberculosis patients in Udupi taluk, Karnataka, India. Methods: A cross-sectional study was conducted with the complete enumeration of all the cases undergoing Directly Observed Treatment Short-course (DOTS) treatment in Primary Health Centre and Community Health Centre of Udupi taluk from March to April 2013. Interview was conducted to obtain the socio-demographic and health information and participants were screened using WHO developed Alcohol Use Disorders Identification Test (AUDIT)Â for alcohol use. Results: Out of 123 participants, 78% were males, 86.2% were Hindu, 79.7% were married and 88.6% were from low socio-economic status. About 20.3% (n=25) participants were alcoholic. Among them, 44% were low risk drinkers, 32% were hazardous drinkers, 4% were harmful drinkers and 20% were alcohol dependent. Age, sex, occupation, tobacco use, perceived health status and discrimination due to tuberculosis positive status were significantly associated with alcohol use. On logistic regression sex, tobacco use, perceived health status and facing discrimination due infectionÂ with tuberculosis were found to be factors associated with alcohol use. Conclusions: This study found a high prevalence of alcoholism among tuberculosis patients which is of concern and has to be addressed. Â Keywords: alcoholism; alcohol use disorder identification test; tuberculosis.